The perceptions and attitudes of vocational and technical students towards the application of mathematics - Lim Ai Lay, Loretta; Khalid, Madihah (Education Technology Centre, University Brunei Darussalam, 2012)
This paper highlights parts of the finding of a larger study which aimed to explore Vocational and Technical Institution (VTI) students’ perceptions and attitudes towards mathematics. Students’ opinions of instructors’ support and behavior towards them, the way these instructors carry out their mathematics lesson and student’ awareness of mathematical application into their respective discipline of study are part of the categorical included in the survey. However this paper only focused on students’ perceptions of and attitudes in general and towards the application of mathematics into the programme that they are undertaking at the VTI. Overall students’ attitudes and perceptions towards mathematics were relatively positive. The analysis revealed that at least one of the qualification level-based comparisons and programme-based comparisons was statistically significantly different on these factors.